Groundwater vulnerability and risk assessment to pollution in Kathmandu - Semkuyu, Dickson John; Thammarat Koottatep; Pandey, Vishnu; Babel, Mukand Singh; Zhou, Yangxiao; Shrestha, Sangam; AIT Fellowship; UNESCO{u2013}IHE; Netherlands Fellowships Programmes (NFP) (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
Groundwater pollution is complex, invisible and has a long - ter m impact. To remediate polluted groundwater is very expensive and often impractical especially for developing countries. Groundwater vulnerability and risk assessment is a useful tool for groundwater pollution prevention and control . This research study was focussed on shallow aquifer groundwater vulnerability and risk assessment to pollution in the groundwater basin of Kathmandu valley , in Nepal. In this study, GIS based DRASTIC model have been used to assess intrinsic and specific aquifer vulnerability to pollution whereas Groundwater Risk assessment Model (GRAM) was used to assess risk to groundwater pollution in the groundwater basin of Kathmandu valley . Seven hydrogeological factors were used in DRASTIC model to produce DRASTIC Index (DI) map which re present intrinsic groundwater vulnerability to pollution of the area. The seven hydrogeological factors used were depth to water, net recharge, aquifer media, soil media, topography, impact of vadose zone, and hydraulic conductivity of aquifer. GIS based G RAM was used to produce likelihood of release of hazards , likelihood of detection of hazards , consequence of hazards and residual risk of groundwater contamination in terms of nitrate in the groundwater basin of Kathmandu valley . It was found that more t han a half of the groundwater basin area of Kathmandu valley is susceptible to groundwater pollution. Also the Northern groundwater district is relatively more vulnerable to pollution than central and Southern ones. However after taking to account the barr iers to groundwater pollution and likelihood of hazards release and detection, it was observed that most areas of the groundwater basin are at moderate residual risk to groundwater pollution . This study provides primary information about vulnerability and risk to pollution for groundwater basin of Kathmandu valley. The findings of this study can be used as a useful tool for managing groundwater resources in Kathmandu valley.
Thesis (M. Eng.) - Asian Institute of Technology - UNESCO-IHE, 2014
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Engineering in Urban Water Engineering and Management at Asian Institute of Technology and the degree of Master of Science in Municipal Water and Infrastructure with specialisation Urban Water Engineering and Management at the UNESCO-IHE
Keywords: Groundwater -- Pollution -- Risk assessment -- Nepal -- Kathmandu